Comparative efficacy and safety of antihyperglycemic drug classes for patients with type 2 diabetes following failure with metformin monotherapy: A systematic review and network meta‐analysis of randomized controlled trials. Issue 4 (8th January 2022) - Zheng, Hui; Sigal, Ronald J.; Coyle, Doug; Bai, Zemin; Johnston, Amy; Elliott, Jesse; Hsieh, Shuching; Kelly, Shannon E.; Chen, Li; Skidmore, Becky; Toupin‐April, Karine; Wells, George A.
Abstract: Aims: To compare the efficacy and safety of antihyperglycemic agents, taken in combination with metformin, for the treatment of type 2 diabetes mellitus (T2DM). Methods: A previous 2016 comprehensive search of Ovid MEDLINE, PubMed, and Cochrane CENTRAL was updated to October 2018, and a systematic review and network meta‐analysis (NMA) was conducted. Randomized controlled trials (RCTs) of patients with T2DM taking an antihyperglycemic agent in combination with metformin were included. Bayesian NMA was performed to assess the relative efficacy and safety of the antihyperglycemic classes. Results: In total, 204 RCTs were included, which assessed the efficacy and safety of eight antihyperglycemic drug classes (i.e., sulfonylureas, meglitinides, alpha‐glucosidase inhibitors, thiazolidinediones, basal and biphasic insulin, dipeptidyl peptidase 4 inhibitors, glucagon‐like‐peptide‐1 receptor agonists and sodium‐glucose cotransport‐2 inhibitors). All drug classes significantly reduced haemoglobin A1c (HbA1c) compared to metformin monotherapy (mean reduction from 0.50 to 0.92). The drug classes varied in their relative effects on hypoglycemia, body weight, body mass index, systolic and diastolic blood pressure, total cholesterol, high and low density lipoprotein cholesterol, and the classes had differing safety profiles on total adverse events, urogenital adverse events, heart failure, serious adverse events, and withdraw due to adverse events. Conclusions: All eight antihyperglycemic drug classes, taken in combination with metformin, reduced HbA1c levels; however, the effects of the agents on other outcomes varied among the classes.